Clinical and Basic Research Progress on Treg-Induced Immune Tolerance in Liver Transplantation - Ni, Xuhao; Wang, Qi; Gu, Jian; Lu, Ling (Frontiers in Immunology, 2021)
Rejection after organ transplantation is a cause of graft failure. Effectively reducing rejection and inducing tolerance is a challenge in the field of transplantation immunology. The liver, as an immunologically privileged organ, has high rates of spontaneous and operational tolerance after transplantation, allowing it to maintain its normal function for long periods. Although modern immunosuppression regimens have serious toxicity and side effects, it is very risky to discontinue immunosuppression regimens blindly. A more effective treatment to induce immune tolerance is the most sought-after goal in transplant medicine. Tregs have been shown to play a pivotal role in the regulation of immune balance, and infusion of Tregs can also effectively prevent rejection and cure autoimmune diseases without significant side effects. Given the immune characteristics of the liver, the correct use of Tregs can more effectively induce the occurrence of operational tolerance for liver transplants than for other organ transplants. This review mainly summarizes the latest research advances regarding the characteristics of the hepatic immune microenvironment, operational tolerance, Treg generation in vitro, and the application of Tregs in liver transplantation. It is hoped that this review will provide a deeper understanding of Tregs as the most effective treatment to induce and maintain operational tolerance after liver transplantation.